2021
DOI: 10.1007/s10072-021-05644-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cognitive reserve: implication for subjective cognitive decline in women

Abstract: Background Subjective Cognitive Decline (SCD) is a self-experienced decline in cognitive capacity with normal performance on standardized cognitive tests, showing to increase risk of Alzheimer’s Disease (AD). Cognitive reserve seems to influence the progression from SCD to Mild Cognitive Impairment (MCI) and to AD. The aim of our study was to investigate gender differences in cognitive reserve evaluating how sex might modulate the role of cognitive reserve on SCD. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
2
14
1
Order By: Relevance
“…In cognitively stable older adults, education was positively associated with brain resilience. These conflicting results highlight differential functions of education on brain health, where in stable older adults ( 37 , 38 ), it serves as a protective factor (which is consistent with previous work), while in cognitively impaired older adults, it has the opposite effect on brain health. More years of education alone in this group did not confer greater brain resilience but instead less.…”
Section: Discussionsupporting
confidence: 77%
“…In cognitively stable older adults, education was positively associated with brain resilience. These conflicting results highlight differential functions of education on brain health, where in stable older adults ( 37 , 38 ), it serves as a protective factor (which is consistent with previous work), while in cognitively impaired older adults, it has the opposite effect on brain health. More years of education alone in this group did not confer greater brain resilience but instead less.…”
Section: Discussionsupporting
confidence: 77%
“…Men had a higher risk of dementia than women possibly due to the observed worse memory in men than in women overall and more specifically beyond age 40 years [ 33 ]. A recent cohort study has demonstrated that education might be more likely to act as a contributor to cognitive reserve in women than in men [ 34 ]. These findings may partly explain why men than women were more prone to develop dementia in later life.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Brow n et al [ 29 ] reported that the association between depression and subjective cognitive decline-related outcomes was regulated by age and gender. A recent study showed that subjective cognitive decline was more common in women than in men, and the score of cognitive complaints in the women group was significantly higher than in the men group [ 30 ]. The symptoms of subjective cognitive decline were assessed by subjective cognitive decline questionnaire-9 (SCD-Q9), where higher scores indicate more symptoms.…”
Section: Discussionmentioning
confidence: 99%